Selectivity of mycoinsecticides and a pyrethroid to the egg parasitoid Cleruchoides noackae (Hymenoptera: Mymaridae) - Domingues, Maurício Magalhães [UNESP]; Becchi, Luciane Katarine [UNESP]; Velozo, Simone Graziele Moio [UNESP]; de Souza, Amanda Rodrigues; Barbosa, Leonardo Rodrigues; Soares, Marcus Alvarenga; Serrão, José Eduardo; Zanuncio, José Cola; Wilcken, Carlos Frederico [UNESP] (Springer Nature, 2020)
Plants of the genus Eucalyptus, cultivated in many countries, have great importance for the world economy. In Brazil, this culture occupies a total of 5.7 million hectares, but native and exotic insect pests can reduce its productivity. Thaumastocoris peregrinus Carpintero & Dellapé (Hemiptera: Thaumastocoridae), an exotic Australian pest, damages Eucalyptus plants. Biological control using the egg parasitoid Cleruchoides noackae Lin & Huber (Hymenoptera: Mymaridae), Heteroptera predators and entomopathogenic fungi, such as Beauveria bassiana and Metarhizium anisopliae, have potential for managing T. peregrinus. Chemical insecticides, including bifenthrin and acetamiprid + bifenthrin, also control this insect. The compatibility of chemical and biological control methods favors integrated pest management. The objective of this study was to evaluate the selectivity of commercial products based on B. bassiana, M. anisopliae and the chemical bifenthrin on the parasitoid C. noackae and its parasitism on T. peregrinus eggs. The selectivity test followed the standards recommended by the International Organization for Biological Control (IOBC). Beauveria bassiana has selectivity to parasitism as well as viability, but was slightly harmful to C. noackae adults; M. anisopliae was innocuous to adults and to the viability of the offspring of this parasitoid, but it reduced the parasitism rate; and bifenthrin did not show selectivity to this parasitoid.